Heterotopic ossifications in revision reverse shoulder arthroplasty and their impact on long-term outcomes - Trefzer, Raphael; Leisner, Michel; Hariri, Mustafa; Weishorn, Johannes; Mick, Paul; Bülhoff, Matthias (Journal of orthopaedic surgery and research, 2025)
Heterotopic ossifications (HO) are frequently observed after joint replacement surgery and may impair joint mobility and clinical outcomes. The incidence and clinical relevance of HO in revision reverse shoulder arthroplasty (RSA) remain unclear. The purpose of this study was to investigate the (1) incidence of HO and (2) the influence of HO on long-term clinical outcomes in a selected patient cohort who underwent revision RSA.
Online veröffentlicht: 8. Oktober 2025
Gesehen am 22.01.2026